A review on laser beam welding of titanium alloys - Auwal, S.T.; Ramesh, Singh; Yusof, Farazila; Manladan, Sunusi Marwana (Springer Verlag, 2018)
In recent years, there is an increased in used of titanium alloys for some parts of mass-produced automobiles and aerospace. However, titanium alloys are characterized by difficult machinability, high melting temperature, high strength, low thermal conductivity, and high reactivity to oxygen, which overshadowed conventional manufacturing processes. To this end, there is a pressing need for more efficient technologies for the manufacture of low-cost titanium structures. Over the years, several joining techniques have been considered for fabrication of titanium alloys. Nevertheless, laser beam welding presents a viable option for welding of titanium due its versatility, high specific heat input, and flexibility. To date, under optimum processing conditions, the strength of the laser-welded titanium alloys can be close to the original material; however, there are still some processing problems such as lower elongation and corrosion resistance coupled with inferior fatigue properties. In this document, the laser beam welding of similar and dissimilar titanium alloys is reviewed, focusing on the influence of the processing parameters, microstructure-property relationship, metallurgical defects, and possible remedies.